Depletion suspends the comparator mechanism in monitoring The role of chronic self-consciousness in sequential self-regulation. [article]. - Jia, Lile
In 4 studies, we accumulated support for the prediction that depletion suspends the comparator mechanism of self-regulatory monitoring. We adopted an individual difference approach and designated chronic self-consciousness as a signature variable for the comparator mechanism. In the nondepletion condition, we found that self-consciousness predicted self-regulation by itself (Study 1), or by interacting synergistically with other motivational factors such as online goal focus (Study 2) and task motivation (Study 3). In the depletion condition, self-consciousness ceased to predict task performance, which suggested that the self-focused comparator mechanism is suspended by depletion. Instead, depleted participants' self-control was predicted by their implicit goal to rest (Study 3), indicating that depletion does not indiscriminately suspend all self-regulatory processes. In Study 4, we showed that when an effective comparator mechanism is counterproductive to task performance, depletion can actually increase task performance. Implications of our findings for the underlying process of depletion as well as models positing ultimate explanations for sequential self-regulation are discussed. -- (from the authors)